THE ROLE OF COMMUNITY NURSE REGARDING CASE DETECTION OF TUBERCULOSIS IN PUBLICE HEALTH CENTER IN BANJARBARU MUNICIPALITY SOUTH BORNEO - Herawati Herawati; Neni Fidya Santi; Zenni Puspitarini (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2014)
Introduction. Tuberculosis is one of the primary communicable diseases in community health problem. Indonesia ranked in 5th position of WHO report in 2009 TB incidence. TB management had already been organized comprehensively regarding case finding and DOTS strategy. Community nurse worked in Public Health Center play an important role in TB management particularly case finding.The aim of this study was to identify community nurse role in case detection of TB in community setting and explore the Active Case finding (ACF) and Extensive Case Finding (ECF) perspective in TB patient detection. Methods. This research used qualitative descriptive study design with in-depth interview. Eight nurses who already worked with TB in Public Health Center in Banjarbaru Municipality South Borneo selected as sample. Study conducted in May – June 2012. Data were analyzed by Miles and Huberman model. Results. The result showed the role of community nurses in the detection passive case finding was waiting for the patient; ACF through home visits and ECF through health education. Nurses in community health centers Banjarbaru City area had been played their role in TB case detection, whether active, passive and extensive. Discussion. They need the full support or participation from government particularly Health Department of related municipality to perform active and extensive case-finding strategies. It is should be integrate with community nursing process. Keywords: The Role Community Nurse, Case Detection, Tuberculosis